The Relevance of Islamic Character Education According “The 7 Habits of Highly Effective People” Book - Siregar, Amy Fitriani; Asyiaty, Ismi Laela; Agustin, Bustanil Ilmi; Hidayat, Nur; Himam, Alin Safaraz (J-PAI: Jurnal Pendidikan Agama Islam, 2024)
This research aims to explore the relevance between the Islamic teachings on character education and the principles put forward by Stephen R. Covey in his book "The 7 Habits of Highly Effective People". The type of this research is a library research with an analytical descriptive approach. The research process involves collecting data related to character education, interpreting the data obtained, and further analyzing and interpreting the data. The results showed that Covey's seven habits, such as being proactive; starting with the end in mind; putting first things first; thinking winning; trying to understand first; then asking to be understood; realizing synergy; sharpening the saw have relevance to Islamic teachings. Although in line, Covey's character education principles are narrower when compared to Islamic teachings that cover the aspects of character and morals more broadly and in detail in the Qur'an and hadith. Islamic character education emphasizes the formation of individuals with strong faith. Overall, this study emphasizes the importance of character education in forming individuals with good personalities, especially in the context of building the Indonesian nation.